La Vaguedad en el lenguaje jurídico (2025)
The language we use on a daily basis presents multiple phenomena and has several characteristics that give content to our expressions. Many times, these characteristics of language enrich the speaker's discourse, which implies a challenge for the listener: the challenge of interpreting. This is the situation that can describe the interpretative work of judges when faced with the task of making decisions regarding a fact that occurs in reality, versus the norms that try to limit the accepted behaviors of society. The judge must take the discourse, in this case the norm, and see if it applies to the situations he is being asked to judge. However, throughout this thesis we want to talk about one of those phenomena that enrich and at the same time can complicate this task: vagueness. This article intends to describe what vagueness is in terms of the problem it can represent in legal language.